2015
DOI: 10.1590/s0102-865020150100000009
|View full text |Cite
|
Sign up to set email alerts
|

Importance of duration and number of ischemic postconditioning cycles in preventing reperfusion mesenteric injuries. Experimental study in rats

Abstract: Ischemic postconditioning was able to minimize reperfusion injury of rats undergone mesenteric ischemia and reperfusion process. There was no difference in the effectiveness of the method comparing two cycles of two minutes with four cycles of 30 seconds by H&E histological evaluation of the ileum after 60-minute reperfusion.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
10
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(10 citation statements)
references
References 20 publications
(21 reference statements)
0
10
0
Order By: Relevance
“…Until now, nearly all studies investigating the effect of IPoC in the intestine, were performed in rats that were anaesthetized by intraperitoneal administration of ketamine and xylazin, and subjected to complete occlusion of the cranial mesenteric artery [4; 7-10; 28; 29]. In these studies, differences in Chiu score of 1 – 2 points were found between the control and treatment groups [4; 7-10], demonstrating greater changes than those found in the current study.…”
Section: Discussionmentioning
confidence: 99%
“…Until now, nearly all studies investigating the effect of IPoC in the intestine, were performed in rats that were anaesthetized by intraperitoneal administration of ketamine and xylazin, and subjected to complete occlusion of the cranial mesenteric artery [4; 7-10; 28; 29]. In these studies, differences in Chiu score of 1 – 2 points were found between the control and treatment groups [4; 7-10], demonstrating greater changes than those found in the current study.…”
Section: Discussionmentioning
confidence: 99%
“…As mentioned, there are few publications aimed at evaluating remote lung damage against IR, especially using IPC as a protection method. Existing publications point to a promising role in this method, similar to other IR situations in which IPC provides tissue protection [ 14 ] . Despite this, there are few studies that have used IPC in clinical practice, which reinforces the importance of finding a pharmacological method that presents the same or greater efficacy, increasing interest in safe drugs such as statins and that at least their pleiotropic effect could be useful in such situations.…”
Section: Discussionmentioning
confidence: 99%
“… 27 Despite this, some algorithms are being praised for mice and rats with low time cycles, like 30 or 10 s, 28 but many results in the literature are conflicting, since the difference between prolonged and shorter cycles is not observed in some studies. 29 , 30 …”
Section: Discussionmentioning
confidence: 99%